2017
DOI: 10.3892/ol.2017.6446
|View full text |Cite
|
Sign up to set email alerts
|

High expression of CCDC25 in cholangiocarcinoma tissue samples

Abstract: Abstract. Cholangiocarcinoma (CCA) is a malignant transformation of biliary epithelial cells. It is a slow growing tumor, but is also highly metastatic with a poor prognosis. Bile acids are known to transactivate the epidermal growth factor receptor (EGFR) in cholangiocytes and induce cyclooxygenase-2 expression. The protein expression profiles of bile acid-treated CCA cells were studied using a proteomic approach. To elucidate the possible mechanisms involved in the bile acid-mediated enhancement of CCA cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 22 publications
3
18
0
Order By: Relevance
“…A previous study reported that CCDC25 was upregulated in CCA tissues when compared with adjacent non-CCA tissues (10). In the present study, a quantitative dot blot assay based on the standard curve created using standard CCDC25 protein was used to reveal that the serum CCDC25 level of patients with CCA was significantly higher compared with that of HCs and patients with BBD.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…A previous study reported that CCDC25 was upregulated in CCA tissues when compared with adjacent non-CCA tissues (10). In the present study, a quantitative dot blot assay based on the standard curve created using standard CCDC25 protein was used to reveal that the serum CCDC25 level of patients with CCA was significantly higher compared with that of HCs and patients with BBD.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, the mechanisms regulating CCDC25 protein expression in CCA cells require further investigation. As CCDC25 was identified as a potential functional protein from the genome database (1215) and only recombinant protein and antibody against it were produced, the biological and physiological functions of CCDC25 is almost unknown (10). Overexpression by gene transfection or depressed production by gene silencing using CCA cells will elucidate the biological role of CCDC25 and possible regulatory mechanisms of its expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment with CA and DCA as BAs induces the migration of CC cells, and CA- and DCA-mediated protein expression profiles identify CCD25 and is significantly upregulated in patients with CC. Also, CCD25 has been associated with the son of sevenless homolog 1 (SOS1) and growth factor receptor-bound protein 2 (GRB2), which are involved in EGFR signaling [ 85 ].…”
Section: Modulators Of Egfr Family Activation In the Progression Omentioning
confidence: 99%
“…Recently, we found that CCDC25 is overexpressed in CCA tissues [ 6 ] and serum CCDC25 level of CCA patients is significantly higher than that of healthy controls [ 7 ]. Moreover, recently one of our colleagues (R.C.)…”
Section: Introductionmentioning
confidence: 99%